Chronological age and reservoir characteristics as predictors of trait composition in Neotropical reservoir fish assemblages. Issue 2 (12th November 2019) - Muniz, Carolina M.; dos Santos, Natália C. L.; Baumgartner, Matheus T.; Agostinho, Angelo A.; Gomes, Luiz C.
Abstract: One of the main impacts on aquatic environments is the alteration of flow regime, usually caused by dam construction. This impact changes the dynamics and functioning of the environment. We aimed to evaluate changes in the composition of functional traits of fish assemblages from 29 reservoirs of different chronological ages. We assessed if there were any alterations in trophic state of these reservoirs according to their ages (chronological variable). Then, we evaluated the relationship between functional traits and environmental/chronological variables. Results showed that reservoir age is a predictor of fish assemblage functional traits composition. In older reservoirs, there was a predominance of omnivorous species, with multiple spawning and parental care. However, herbivorous species, with total spawning and medium size, had their abundance reduced. Also, it was possible to identify the influence of depth and water retention time on the composition of functional traits. By showing that although age has an influence on composition, the intrinsic characteristics of each reservoir are very important in evaluating the impacts of these projects. Therefore, the findings presented provide insights into what may happen to functional traits of fish assemblages with ageing of reservoirs.